Encapsulated Mesenchymal Stromal Cell Microbeads Promote Endogenous Regeneration of Osteoarthritic Cartilage Ex Vivo. Issue 8 (12th January 2021) - Sahu, Neety; Agarwal, Pranay; Grandi, Fiorella; Bruschi, Michela; Goodman, Stuart; Amanatullah, Derek; Bhutani, Nidhi
Abstract: The anti‐inflammatory secretome of mesenchymal stromal cells (MSCs) is lucrative for the treatment of osteoarthritis (OA), a disease characterized by low‐grade inflammation. However, the precise effects of the MSC secretome on patient‐derived OA tissue is lacking. To investigate these effects, alginate encapsulated MSCs are co‐cultured with patient‐derived OA cartilage explants for 8 days. Proteoglycan distribution in OA cartilage explants examined by Safranin O staining is markedly improved when cultured with MSC microbeads as compared to control OA explants cultured alone. Total sulfated glycosaminoglycan (sGAG) content in OA explants is significantly increased upon co‐culture with MSC microbeads on day 8. The sGAG released into the culture media is unchanged by the presence of MSC microbeads, suggesting de novo sGAG synthesis in OA explants. Co‐culture with MSC microbeads increased the DNA content and Ki67 + cells in OA explants, indicating proliferation. An increase in secreted cytokines IL‐10, HGF, and sFAS assessed by multiplex cytokine assay, increased TIMP1 levels, and reduction in percent apoptotic cells in OA explants is noted. Together, data demonstrates that paracrine factors secreted by alginate encapsulated MSCs microbeads in response to OA cartilage, create an anabolic, proliferative, and anti‐apoptotic microenvironment inducing endogenous regeneration in clinically relevant, patient‐derived OA cartilage. Abstract : Microfluidics‐based encapsulation of MSCs in alginate hydrogel is utilized to study the paracrine effects of MSCs when primed to patient‐derived osteoarthritic cartilage. In ex vivo co‐cultures, alginate encapsulated MSC microbeads orchestrate an anabolic, proliferative, and anti‐apoptotic microenvironment that promotes endogenous regeneration in clinically relevant, patient‐derived osteoarthritic cartilage.